2011
DOI: 10.15241/bhh.1.2.143
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Teach: Teaching Internships in Counselor Education and Supervision

Abstract: Aligning with a particular theoretical orientation or personal multi-theory integration is often a formidable task to entry-level counselors. A better understanding of how personal strengths and abilities fit with theoretical approaches may facilitate this process. To examine this connection, thirty-five mental health professionals completed a series of inventories to determine if passive counselors adhere to more nondirective, insight-oriented theories, while assertive counselors adhere to more directive, act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…These experiences are usually offered as semester‐long courses or seminars (ACES Teaching Initiative Taskforce, 2016). Our literature review identified only one study in support of formal coursework as a teaching preparation practice (Hunt & Weber‐Gilmore, 2011), with others reporting it as unhelpful in strengthening perceived preparedness for teaching (Hall & Hulse, 2010), self‐efficacy toward teaching (Olguin, 2004; Tollerud, 1990), and preparedness for the actual teaching responsibilities of a counselor educator (Waalkes et al, 2018).…”
Section: Teaching Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…These experiences are usually offered as semester‐long courses or seminars (ACES Teaching Initiative Taskforce, 2016). Our literature review identified only one study in support of formal coursework as a teaching preparation practice (Hunt & Weber‐Gilmore, 2011), with others reporting it as unhelpful in strengthening perceived preparedness for teaching (Hall & Hulse, 2010), self‐efficacy toward teaching (Olguin, 2004; Tollerud, 1990), and preparedness for the actual teaching responsibilities of a counselor educator (Waalkes et al, 2018).…”
Section: Teaching Preparationmentioning
confidence: 99%
“…There is a lack of research on what experiences most effectively prepare CES doctoral students to teach (Barrio Minton, Wachter Morris, & Bruner, 2018). Current literature regarding the training of CES doctoral students to teach consists primarily of descriptive or qualitative studies (e.g., Baltrinic et al, 2016; Barrio Minton & Price, 2015; Hunt & Weber‐Gilmore, 2011; Orr et al, 2008; Waalkes et al, 2018) with a dearth of quantitative research on the topic. The few existing quantitative studies have addressed the influence of teaching preparation on CES doctoral students’ self‐efficacy toward teaching (Olguin, 2004; Tollerud, 1990) and counselor educators’ self‐reported preparedness to teach given their doctoral‐level teacher training experiences (Hall & Hulse, 2010).…”
Section: The Current Studymentioning
confidence: 99%
“…Coteaching is a systematic approach that has been used for decades for preparing doctoral students to teach in teacher training programs (Badiali & Titus, ; Crow & Smith, ) and more recently in counselor education programs (Hunt & Weber Gilmore, ; Malott, Hrindaya Hall, Sheely‐Moore, Krell, & Cardaciotto, ; Orr, Hall, & Hulse‐Killacky, ). Coteaching involves two teachers, usually one experienced and one beginner, (a) working side by side to enhance teachers' learning opportunities, (b) encouraging mutual insights into the teaching process (Badiali & Titus, ), and (c) socializing the responsibility for preparing new teachers as shared among professionals (Crow & Smith, ).…”
mentioning
confidence: 99%
“…Findings from existing studies support teacher preparation practices, including teaching an entire course, teaching under the supervision of an experienced faculty member, participating in a teaching practicum to better prepare for teaching roles (Hall & Hulse, ), developing a personal style or philosophy of teaching, shifting roles from teaching assistant to lead instructor through supervision, and increasing doctoral students' confidence and competence as teachers (Orr et al, ). Hunt and Weber Gilmore () found that a combination of didactic training and a coteaching internship helped doctoral students to develop course materials, manage classroom behavior, and develop a teaching style and philosophy.…”
mentioning
confidence: 99%
See 1 more Smart Citation